The Innovative Educational Thought of Jane Roland Martin: A Review Essay. Issue 1 (27th June 2018) - Mulcahy, D. G.
ABSTRACT: D. G. Mulcahy highlights some of Jane Roland Martin's major contributions to the field of philosophy of education in this review essay. He focuses on several of Martin's better‐known works — including Reclaiming a Conversation, The Schoolhome, Changing the Educational Landscape, Coming of Age in Academe, Educational Metamorphoses, and School Was Our Life — tracing through them the development of her reconceptualization of the idea of a liberal education from the early1980s to the present day. Viewing Martin's contribution from the perspective of liberal education, he contends, underscores the optimistic spirit of her work as well as its originality and significance for the theory of education as a whole. Mulcahy gives particular attention to these elements of Martin's thought: the importance she attributes to educating the young for active participation in the world and not mere observation of it; her analysis of the range and complexity of our cultural wealth; her concept of a gender‐sensitive education; and her emphasis on the unique contribution of the experience of women to education. Martin's substantial body of work, Mulcahy concludes, stands as a compelling alternative to mainstream educational theorizing, one that offers hope for the potential of educational renewal.